The influence of a computing resource on the initial literacy process: A study with third grade preschool children - Calderón Guerrero, Gabriela; Pohls Díaz, Elizabeth (IE Revista de Investigación Educativa de la REDIECH, 2021)
The frame of reference that supports this research is the constructivist one. Research design: quasi-experimental with descriptive and correlational scope. Aim: to determine if the proposed computing resource (educational software) significantly encouraged the initial literacy. 20 third-year preschool children from a Mexican public school were interviewed. Experimental and control groups were formed, taking care that they were similar in various aspects, including their knowledge about the writing system. Both groups were evaluated on their knowledge about the writing system at the beginning (to form the experimental and control groups), in the middle and at the end of the research. The experimental group, during a period of four months twice a week (20 minutes per session), worked with the software, while the control group did not. Results: before using the software, both groups showed the same writing levels; from the second and third evaluation, when the experimental group started using the software, a significant difference was observed between both groups, favoring the experimental group. The results suggest that the use of new technologies, with precise didactic approaches, favored the initial literacy process of the population studied.